Mechanisms of microbial photoinactivation by curcumin’s micellar delivery - Ryu, Victor; Ghoshal, Mrinalini; Chuesiang, Piyanan; Ruiz-Ramirez, Silvette; McLandsborough, Lynne; Corradini, Maria G. (Frontiers in Food Science and Technology, 2024)
Introduction: Microbial photoinactivation using UV light can be enhanced by the addition of food-grade photosensitizers (PSs), such as curcumin. Micellization of curcumin can improve its stability and antimicrobial activity. The objective of this study was to investigate the potential mechanisms that contribute to the photoinactivation of Escherichia coli O157: H7 and Listeria innocua by curcumin-loaded surfactant solutions produced with Surfynol 465 (S465) or Tween 80 (T80) below, near, and above their critical micelle concentration (CMC). Methods: Stock curcumin-surfactant solutions were produced with S465 or T80 (5 mM sodium citrate buffer, pH 3.5). Mixtures of each bacterial suspension (initial inoculum = 6 LogCFU/mL), 1 µM curcumin, and surfactants were irradiated with UV-A light (λ = 365 nm) for 5 min. Microbial recovery after treatments was assessed by monitoring the growth of the treated E. coli O157: H7 or L. innocua using an oCelloscope™. The growth curves were characterized using a modified logistic model. Results and Discussion: Both gram-positive and gram-negative bacteria showed less and slower recovery when treated with curcumin-S465 (near or at CMC) than curcumin-T80 solutions after irradiation. FLIM micrographs suggested that curcumin was preferentially localized at the cell membrane when S465 was present, as evidenced by its longer lifetimes in samples treated with curcumin-S465 solutions. Washing after treatment resulted in the removal of loosely bound or unbound S465-curcumin micelles; hence, both E. coli O157: H7 and L. innocua recovery was faster. This suggested that curcumin partitioning has a significant role in microbial photoinactivation, possibly due to the production of reactive oxygen species (ROS) closer to/within the membrane. The permeability of the membrane of E. coli O157: H7, as inferred from the Live/Dead cell assay, increased when S465 was present, suggesting that S465 can also facilitate inactivation by disrupting the membrane and by favoring the localization of curcumin adjacent to the cell membrane. Therefore, a synergistic antimicrobial effect is observed when curcumin is present alongside S465 at concentrations below or near its CMC due to the disruption of the cell membrane by S465.